Wiman-type inequality for functions analytic in a polydisc - Kurylyak, A. O.; Skaskiv, O. B.; Shapovalovs’ka, L. O. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We prove an analog of Wiman-type inequality for analytic functions in a polydisc $\mathbb{D}^p = \{z \in \mathbb{C}^p : |z_j| < 1,\; j \in \{ 1, . . . ,p\} \} , p \in N.$ The obtained inequality is sharp.